Single-Step Green Synthesis of Iron Nanoparticles in the Aqueous Phase for Catalytic Application in Degradation of Malachite Green - Rathore, Ajay; Vijay Devra (Advanced Energy Conversion Materials, 2021)
The goal of the research was to devise a simple and environment-friendly approach to synthesize iron nanoparticles (FeNPs) and evaluate the catalytic activity of biosynthesized FeNPs for the degradation of the cationic dye Malachite Green (MG) in the presence of Peroxomonosulphate (PMS). Different instrumental approaches were used to characterize green produced FeNPs, and the results show that the NPs are spherical and 48 nm in size. Increasing the concentrations of nanoparticles (0.5 × 10-8 - 2.0 × 10-8 mol/dm3), Peroxomonosulphate (1.0 × 10-4 - 5.0 × 10-4 mol/dm3), dye (1.0 × 10-5 - 5.0 × 10-5 mol/dm3), pH (5), and high temperature (25-35 °C) enhanced the degradation kinetics of Pseudo-first-order kinetics were used to describe the degradation of MG in the FeNPs/PMS system, and activation parameters were derived. The maximum MG degrading efficiency for the FeNPs/PMS system was 88% in 60 minutes under optimum reaction conditions. The structure of intermediates formed by MG degradation by FeNPs/PMS was determined using UV-vis spectrum analysis. The application of synthesized FeNPs to improve Peroxomonosulphate oxidation potential for MG degradation is a unique, efficient, promising, and eco-friendly technology because it does not require any expensive reagents.